2022
DOI: 10.1073/pnas.2116865118
|View full text |Cite
|
Sign up to set email alerts
|

The synthetic artificial stem cell (SASC): Shifting the paradigm of cell therapy in regenerative engineering

Abstract: Stem cells are of great interest in tissue regeneration due to their ability to modulate the local microenvironment by secreting bioactive factors (collectively, secretome). However, secretome delivery through conditioned media still requires time-consuming cell isolation and maintenance and also may contain factors antagonistic to targeted tissue regeneration. We have therefore engineered a synthetic artificial stem cell (SASC) system which mimics the paracrine effect of the stem cell secretome and provides t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…Moreover, Shah et al used growth factors important to chondrogenesis and encapsulated recombinant proteins in poly (lactic-coglycolic acid) 85:15 (PLGA) to fabricate a synthetic artificial stem cell (SASC) system. After injecting SASC, it dramatically reduced the NO contents and gene expression levels of ADAMTS5 and the proteoglycan 4 (PRG4) genes in the OA rodent model, thereby demonstrating significant anti-inflammatory and chondroprotective effects [ 133 ].…”
Section: No In Oa Treatmentmentioning
confidence: 99%
“…Moreover, Shah et al used growth factors important to chondrogenesis and encapsulated recombinant proteins in poly (lactic-coglycolic acid) 85:15 (PLGA) to fabricate a synthetic artificial stem cell (SASC) system. After injecting SASC, it dramatically reduced the NO contents and gene expression levels of ADAMTS5 and the proteoglycan 4 (PRG4) genes in the OA rodent model, thereby demonstrating significant anti-inflammatory and chondroprotective effects [ 133 ].…”
Section: No In Oa Treatmentmentioning
confidence: 99%
“…Many studies have revealed that the therapeutic effect of non-tendon MSCs is mainly due to the ability of resident cells to be endowed by paracrine mechanisms or intercellular communication ( Daneshmandi et al, 2020 ; Chen et al, 2021b ; Shah et al, 2022 ). The MSCs regulate inflammation by secreting cytokines and stimulate AT tissue growth by secreting exosomes ( Shi et al, 2019 ; Yu et al, 2020 ).…”
Section: Tissue Regeneration Strategies For Achilles Tendon Injury Tr...mentioning
confidence: 99%
“…Most often, core–shell or layer-by-layer deposition of the biochemicals is used to avoid post-implantation ‘burst’ release. Recently, in the Laurencin group, a novel artificial stem cell mimicking system is developed (synthetic artificial stem cells) with the capability to deliver the target-specific secretomes to regulate chondrogenesis in the OA treatment [ 75 ]. Similarly, extracellular vesicles (EVs) released by mesenchymal stem/stromal cells, recently grabbed the attention in view of their regulatory capabilities in targeted bone and cartilage regeneration.…”
Section: Current Challenges In Osteochondral Defect Regenerationmentioning
confidence: 99%